Fluoxetine and Risk of Bleeding in Patients Aged 60 Years and Older Using the Korea Adverse Event Reporting System Database: A Case/Noncase Study. Issue 4 (July 2019) - Kim, Seonji; Ko, Young-Jin; Park, Kyounghoon; Yang, Bo Ram; Kim, Mi-sook; Park, Byung-Joo
Abstract: Background: Depression, the leading cause of nonfatal disease burden, has a strong correlation with suicide and affects approximately 7% of the general elderly population. Adverse drug reactions in older patients are particularly important because of reduced drug metabolism, polypharmacy, drug-drug interactions, and drug-disease interactions. Fluoxetine is the first representative selective serotonin reuptake inhibitor but is associated with the possibility of hemorrhage based on its mechanism of action. Serious cases of gastrointestinal bleeding and cerebral hemorrhage have been reported, raising concerns about the safety of this drug. Methods: We detected signals of bleeding risk associated with fluoxetine in an elderly population using the Korea Adverse Event Reporting System database. Reporting odds ratios and 95% confidence intervals (CIs) were calculated. Results: A total of 16, 517 adverse events related to antidepressants were reported. The reporting odds ratios for fluoxetine were 2.34 (95% CI, 1.03–5.34) for total bleeding, 4.41 (95% CI, 1.60–12.15) for major bleeding, 2.06 (95% CI, 0.28–15.03) for gastrointestinal bleeding, and 6.12 (95% CI, 2.14–22.60) for brain hemorrhage compared with those of all other antidepressants. Conclusions: We detected safety signals with total bleeding, major bleeding, and brain hemorrhage related to fluoxetine. For patients with a high risk of bleeding, such as the elderly population, prescribing antidepressants other than fluoxetine can be considered. The results of this study provide preliminary evidence of a relationship between fluoxetine and hemorrhage but have wide 95% CIs. Further pharmacoepidemiological studies will be needed to confirm the risk of bleeding associated with fluoxetine.